PENGENALAN TEKNOLOGI KOMPUTER DAN JARINGAN DASAR SEBAGAI SARANA PENINGKATAN PENGHETAHUAN SISWA/SISWI SMP MKGR SEPATAN - Muhamad Albana; Muhamad Bahron; Muhammad Ricky Ardian; Muhammad Bintang Fitriansyah; Muhammad Iqbal Nurdianto; Syahrul Wardi; Yayat Supriatna; Adam Widayat; Abdullah Wahid Abi; Okta Irawati (Abdi Jurnal Publikasi, 2025)
Introduction to computer technology and basic networking is a crucial step in enhancing students' knowledge, particularly at SMP MKGR Sepatan. With rapid technological advancement, understanding hardware, software, and computer networks has become essential for preparing young generations to face workforce challenges. This study aims to assess the effectiveness of teaching computer technology and basic networking in improving students' knowledge. Through a tailored curriculum and interactive learning, students are expected to grasp fundamental concepts of computer networks, computer operations, and troubleshooting common system issues. The findings indicate that introducing basic computer technology and networking not only enhances students' technical skills but also fosters a positive attitude toward information technology, which can be applied both in daily life and the professional world. Therefore, integrating computer technology and basic networking into the curriculum at SMP MKGR Sepatan is vital in preparing students for the digital era.